Hyaluronic acid efficacy in root coverage procedures: a systematic review and meta-analysis - Mohammadreza Talebi Ardakani; Anahita Moscowchi; Amir Talebi; Mohammad Hossein Talebi (BMC Oral Health)
Abstract Background Treatment of gingival recessions through surgical approaches is a common periodontal intervention. There is a rise in using biologics in root coverage procedures. As it has been shown that hyaluronic acid (HA) promotes wound healing, this review aimed to assess its efficacy in the treatment of gingival recessions. Methods An electronic search was conducted across several databases (Medline/ PubMed, Embase, Scopus, Web of Science) supplemented by manual searching. The effectiveness of using HA was evaluated using various outcome measures, with the primary indicators being complete and mean coverage, recession depth, and recession width. Meta-analysis was performed to estimate the differences between test and control sites. Results A total of 9 studies were eligible for inclusion. The overall analysis showed no significant difference between coronally advanced flap (CAF) + HA and control groups (CAF alone or CAF + sub-epithelial connective tissue graft) in terms of mean root coverage with a mean difference of 8.23 (95% confidence interval -3.06 to 19.53) and p = 0.12. Conclusions The current evidence suggests that the local application of HA may have some slight benefits over CAF alone in certain parameters. Nevertheless, its application does not add significant benefits to connective tissue graft. Given the high heterogeneity among the studies, further research with extended follow-up periods is necessary to better understand the clinical implications of using hyaluronic acid in this context. Trial registration CRD42024580649